Quinine sulfate and bacterial invasion - Tufano Maria Antonietta; Ruocco Eleonora; Donnarumma Giovanna; Greco Rita; Baroni Adone; Wolf Ronni; Ruocco Vincenzo (BMC, 2002)
Abstract Background As many patients who receive antimalarial drugs for treatment of noninfectious, inflammatory diseases are also immunosuppressed and might have a concomitant bacterial infection, we studied the effectiveness of these drugs against bacterial infections, to find out whether they could protect against (and even treat) such conditions and obviate the need for an additional antibiotic drug. Methods Effect of QS on bacterial growth: Escherichia coli (E. coli) HB101 pRI203 were cultured overnight at 37°C in TSB and inoculated (approx 1 × 107 cells /ml) in MEM in the presence of QS at various concentrations (0, 50 and 100 μM). The effect of QS at concentration of 50 and 100 μM on the entry process of E. coli HB101 pRI203 into HeLa cells was studied under different experimental conditions: 1. QS was incubated with 3 × 105 HeLa cells for 60 min at 37°C prior to infection. 2. QS was added to HeLa cell monolayers during the infection period. Results QS showed no antibacterial activity after 24 h of incubation. The invasive efficiency of the bacteria was significantly inhibited at a dose-dependent manner, when QS was added to HeLa cells for 60 min at 37°C prior to infection (condition 1), and to a lesser extent when added during the period of infection (condition 2). Conclusions Although the antimalarials are generally regarded as being inactive against most extracellular bacterial species, our results indicate that QS significantly inhibited the internalization/invasion efficacy of E. coli in the host cells.